2016
DOI: 10.1002/anie.201608500
|View full text |Cite
|
Sign up to set email alerts
|

A Metallaanthracene and Derived Metallaanthraquinone

Abstract: Metalla-analogues of archetypal aromatic molecules are attracting ever increasing interest. Although metallabenzenes (which fall within this class) have been well studied, fused-ring metallabenzenes are rare and of the linear polycyclic metallaaromatic hydrocarbons, only metallanaphthalene is known. Herein we report the first metallaanthracene, [Ir(C H {CH CO Me-5})Cl(PPh ) ]O SCF (5), which represents the next member of this series of polycyclic compounds. Structurally, 5 has a number of features in common wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 36 publications
(25 reference statements)
1
66
0
Order By: Relevance
“… Diels–Alder cycloaddition reaction between iridaanthracene 1 and maleic anhydride reported by Frogley and Wright (see ref. ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“… Diels–Alder cycloaddition reaction between iridaanthracene 1 and maleic anhydride reported by Frogley and Wright (see ref. ).…”
Section: Introductionmentioning
confidence: 97%
“…Very recently, Frogley and Wright successfully prepared the first metallaanthracene complex, the iridaanthracene 1 (Scheme ), which can be considered as a novel polycyclic aromatic hydrocarbon including a transition‐metal fragment in its structure . According to the available structural and spectroscopic data, it is suggested that the transition‐metal fragment induces a significant influence on the π‐system of the molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported metallacycles includem etallabenzenes, [1,2] metallabenzynes, [3,4] metallaannulenes, [5] and other metallacycles. Reported metallacycles includem etallabenzenes, [1,2] metallabenzynes, [3,4] metallaannulenes, [5] and other metallacycles.…”
Section: Introductionmentioning
confidence: 99%
“…Metalla‐analogues of conventional organic aromatic compounds, in which a transition metal and its ancillary ligands formally replace one carbon atom, have attracted considerable interest recently . Although the isolation and study of a considerable number of metallabenzenes and fused‐ring metallabenzenes has been reported, much remains to be explored regarding the reactivity of these compounds.…”
Section: Introductionmentioning
confidence: 99%